Pentingnya Pendidikan Jasmani Olahraga Dan Kesehatan Terhadap Perkembangan Anak Di SD Swasta Al-Washliyah Kabupaten Deli Serdang - Windi Putri Arisqa; Fitri Syakira Ridwan; Reyhan Prayudha; Suyono Suyono (Journal on Education, 2024)
Education will not be complete without physical education, society cannot be separated from physical education because one of the main benefits of physical education is that it can make the body healthy and strengthen the body’s muscles, which can be done through exercise and other activities. The purpose of this research is to find out how the process of physical education is carried out by the school. This research uses a qualitative method with a descriptive approach through observation, interviews and documentation instruments. From the research results, it was found that the physical education process carried out by the school was that PJOK learning was important to increase student activity and become a structured direction for students’ movement activities.